Perspective on clinical and imaging tools for early identification of temporomandibular joint involvement in juvenile idiopathic arthritis - Silvia Magni-Manzoni (Exploration of Musculoskeletal Diseases, 2025)
The temporomandibular joint (TMJ) involvement is an underestimated feature of juvenile idiopathic arthritis (JIA) since it is usually asymptomatic at presentation for an undeterminable time. Late diagnosis of TMJ arthritis in JIA patients leads to delayed treatment, long-term orofacial disturbances, and impaired health-related quality of life (HRQOL). Therefore, the detection of TMJ involvement is fundamental and represents a challenge. This perspective presents state-of-the-art current initiatives and available tools for early diagnosis of TMJ arthritis in children with JIA. Standardized protocols and multidisciplinary efforts for improving clinical skills in the assessment of TMJ in JIA are presented and commented on. An overview of imaging efforts for early detection of TMJ involvement in JIA is also provided, with a critical review of the advantages and limitations of different techniques, imaging protocols, and scoring systems. The perspective offers insights into the correct use and improvement of available and potential tools for early identification of TMJ arthritis in JIA subjects who deserve timely multidisciplinary treatment, avoiding both underestimation and over-diagnosis of TMJ arthritis in routine clinical practice.